Aplikasi Pemodelan 3 Dimensi Router Mikrotik RB433AH. RB450, RB800, RB951G-2HnD dan Haplite Berbasis Augmented Reality dan Firebase - Yohanes Kurniahu (Jurnal Informatika dan Multimedia, 2018)
MikroTik is a company engaged in internet service providers and internet service connectors from wireless internet service providers, a lot of use and utilization of MikroTik products. MikroTik products for example are RB433AH Router Board and RB951g-2hnd. This RB433AH Router Board and RB951g-2HnD are used by Kediri Polytechnic students as learning media for subjects related to Computer Networks, while RB450, RB800 and hAP lite are used for Access Points. However, there is a problem when the system reset function on the application is not successfully executed so it must reset by hardware reset on the Router Board. The method of operation of devices connected to the Router Board such as LAN cables, antennas, LAN Cards and PCIE for the first time is used for laymen who still do not understand, so a solution is needed to inform the user how to operate the RB433AH and RB951G-2HND routers. Therefore, an application is prepared that can scan images and then display the 3-dimensional model of the Router in Augmented Reality to help the operation of the RB433AH Router Board and RB951G-2HND and present the comments section for problem solving. Applications are presented in mobile devices by utilizing Vuforia Augmented Reality and Realtime Databases from Firebase.